1994
DOI: 10.1152/jappl.1994.76.3.1144
|View full text |Cite
|
Sign up to set email alerts
|

Catecholamine and blood lactate responses to incremental rowing and running exercise

Abstract: Ten collegiate rowers performed discontinuous incremental exercise to their tolerable limit on two occasions: once on a rowing ergometer and once on a treadmill. Ventilation and pulmonary gas exchange were monitored continuously, and blood was sampled from a venous catheter located in the back of the hand or forearm for determination of blood lactate ([La]) and plasma epinephrine ([Epi]) and norepinephrine ([NE]) concentrations. Thresholds for lactate (LT), epinephrine (Epi-T), and norepinephrine (NE-T) were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 30 publications
0
31
1
1
Order By: Relevance
“…The underlying mechanism has not been clarified, but it may depend on exercise intensity and duration exercise. Some papers showed that lactate threshold or sympathetic drive may be a critical intensity to elicit acute fibrinolytic changes in tPA (Davis et al, 1976;Wheeler et al, 1986;Weltman et al, 1994). In the present study, the increase in lactate and NOR concentration after exercise with KAATSU was much higher than that without KAATSU.…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…The underlying mechanism has not been clarified, but it may depend on exercise intensity and duration exercise. Some papers showed that lactate threshold or sympathetic drive may be a critical intensity to elicit acute fibrinolytic changes in tPA (Davis et al, 1976;Wheeler et al, 1986;Weltman et al, 1994). In the present study, the increase in lactate and NOR concentration after exercise with KAATSU was much higher than that without KAATSU.…”
Section: Discussioncontrasting
confidence: 43%
“…However, the further increase in tPA activity or antigen was observed in the exercises combined with KAATSU. It has been reported that the fibrinolytic responses to exercise are related to changes in plasma lactate and /or NOR (Davis et al, 1976;Wheeler et al, 1986;Weltman et al, 1994;Hilberg et al, 2003b). The underlying mechanism has not been clarified, but it may depend on exercise intensity and duration exercise.…”
Section: Discussionmentioning
confidence: 99%
“…These, in turn, have been linked to several processes that contribute to fatigue, including the accelerated breakdown of creatine phosphate (McCann, Mollé, & Caton, 1995), the inhibition of glycolysis and glycogenolysis (Spriet, Lindinger, McKelvie, Heigenhauser, & Jones, 1989), the inhibition of lipolysis (Boyd, Giamber, Mager, & Lebovitz, 1974) and the interference with the calcium triggering of muscle contractions (Favero, Zable, Bowman, Thompson, & Abramson, 1995). In addition, lactic acidosis stimulates the release of catecholamines (Goldsmith, Iber, McArthur, & Davies, 1990), and thus the lactate threshold has been found to occur in close proximity to a catecholamine threshold (Urhausen, Weiler, Coen, & Kindermann, 1994;Weltman et al, 1994). In turn, catecholamines have widespread effects that further push the organism towards its functional limits, including a breakpoint in the relationship between the rate -pressure product and work rate (Riley et al, 1997;Tanaka et al, 1997).…”
Section: Domain Of ''Heavy'' Intensitymentioning
confidence: 99%
“…In groups C and D, pH at peak exercise was influenced by both carbon dioxide retention and arterial lactate level, because an increase in lactate and a decrease in HCO 3 -, related to the increase in oxygen uptake, were detected, and carbon dioxide retention was not detected in group D, like that in a healthy subject. 11 However, the arterial pH at peak exercise was mainly due to carbon dioxide retention in groups A and B, which could have been caused by limitation of increase of tidal volume (ie, the decrease in alveolar effective ventilation), and the effect of lactic acidosis was small.…”
Section: Exercise-induced Acidosis and Contributing Factorsmentioning
confidence: 92%
“…The severity of dyspnea rapidly increases at work rates above the lactic threshold, and plasma norepinephrine and epinephrine also increase in a similar manner during exercise. 10,11 However, we have observed that in some COPD patients with severely reduced exercise capacity, lactic threshold cannot be detected methodologically by estimating the concentration of plasma lactate using the log-log transform of the lactateoxygen uptake relationships in cardiopulmonary exercise testing in clinical practice. 12 Peak oxygen uptake during incremental cardiopulmonary exercise testing, FEV 1 , and body mass index (BMI) are predictors of mortality in COPD patients.…”
Section: Introductionmentioning
confidence: 99%